Ὁ ἁγιώτα(τος) μ(ητ)ροπολίτης Λακεδαιμονίας κ(αὶ) ᾽Εθνικ[ῶν] ὑπ(έ)ρτιμος ὁ Εὐγένειος: ᾽᾽Ένα επιγραφικό unicum από τη μητρόπολη του Μυστρά - ΒΑΧΑΒΙΩΛΟΣ Δημήτριος (Byzantina Symmeikta, 2025)
In this paper we attempt to re-examine the inscription that identifies the figure of Eugenios, metropolitan of Lacedaemonia, which has depicted in diaconal of St. Dimitrios, the metropolis of Mystras. We re-examine, in particularly, its content in relation to the ecclesiastical history of the Southern Peloponnese during its recovery from the troops of Michael VIII Palaiologos. In this way, it is hoped that valuable information will emerge on the ecclesiastical and not only the history of at least part of the southern Peloponnese during the reign of Michael VIII Palaiologos. It is, however, still to be investigated whether and to what extent what lies behind the inscription in question influenced the ecclesiastical geography of the southern Peloponnese even in the period after the Fall of Constantinople.